Effects of new openings on the in/plane behaviour of unreinforced brick masonry walls - Vera, M. Y. O. (2018)
Existing brick masonry buildings are frequently modified to satisfy nowadays living demands. Such modifications may include new windows or doors that connect two rooms and require openings to be cut from load bearing walls. In current design practice, these interventions are generally designed and verified for vertical load, but the structural behavior of these altered walls when submitted to in-plane loads (due to seismic actions) is not yet fully understood. Thus, design practice may be inaccurately estimated. The objective of this work is to evaluate, numerically and experimentally, the effects of introducing openings in masonry solidbrick walls subjected to in-plane loading. Three main parameters are considered for the numerical studies: i) walls dimensions, ii) opening type, iii) opening size. As expected, results show that walls with medium-large openings are the most vulnerable case-scenario. These numerical results have addressed the design of a representative wall tested at the University of Brescia. The preliminary results of this experimental program are included in this paper